Mn(II) and Zn(II) Complexes of a Coumarin Derivative: Synthesis, Characterization and Biological Potential - Shahid, Z.A.; Tabassum, R. (Eurasian Journal of Chemistry, 2025)
This study focused on the synthesis, characterization and biological evaluation of coumarin derivatives and their metal complexes. The synthesized compounds were characterized using spectroscopic techniques, including FTIR, 1H NMR, 13C NMR, X-ray diffraction (XRD), and thermal analysis, with mass spectrometry confirming their molecular weights. Notably, the XRD analysis revealed crystal sizes of 4.092 nm for ZL16, 4.34 nm for ZL16Mn, and 1.57 nm for ZL16Zn. FTIR analysis confirmed the presence of the –N=N– group, and comparative UV-Visible spectra validated the successful synthesis of new coumarin compounds. Antibacterial activity of synthesized compounds was evaluated against gram-negative and gram-positive bacteria using the disc diffusion method, with inhibition zones ranging from 7–31 mm, compared to the standard drug Amikacin, which had a zone of 15 mm. Antioxidant activity was assessed with IC50 values between 5.65– 11.84 μg/mL for DPPH and 5.89–11.20 μg/mL for NO, compared to ascorbic acid. Molecular Docking analysis revealed strong binding interactions between the synthesized compounds and the Mannosyl-oligosaccharide glucosidase and Oligo-1,6-glucosidase enzymes, with binding energies ranging from –9.8 to –10.9 kcal/mol. These findings contribute to the field of medicinal chemistry, highlighting the potential of these compounds as therapeutic agents. Further investigations are required at molecular level to explore their full therapeutic potential.
Keywords: coumarin derivatives; manganese; zinc metal complexes; antioxidant activity; antibacterial activity; molecular docking; X-ray diffraction; thermal analysis; antidiabetic